Cobalt sulfide modified iron-based perovskite composite catalyst and preparation method and application thereof
By growing CoS2 and CoFe2O4 in situ on the surface of LaFeO3 perovskite catalyst, a cobalt sulfide-modified iron-based perovskite composite catalyst is formed, which solves the problem of poor degradation of antibiotic pollutants by traditional perovskite catalysts and achieves efficient antibiotic wastewater treatment.
Patent Information
- Application Number
- CN202411846285.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-25
Smart Images

Figure CN119680580A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of wastewater pollution and environmental restoration, and specifically relates to a cobalt sulfide modified iron-based perovskite composite catalyst and a preparation method and application thereof. Background Art
[0002] With the acceleration of industrialization, antibiotics are widely produced and used, and their residues will enter the environment through various pathways, posing a serious threat to the ecological environment and human health. Therefore, it is of great significance to develop a new and efficient antibiotic pollution treatment technology. Advanced oxidation technology (AOPs) can produce reactive oxygen species (ROS) to achieve the degradation and mineralization of antibiotic pollutants. Among them, persulfate-based advanced oxidation processes (PS-AOPs) stand out with their advantages such as strong oxidation performance, low operating costs and wide pH adaptability. Heterogeneous transition metal catalysts are one of the most economical, effective and convenient methods to achieve persulfate activation.
[0003] Multi-component catalysts are composed of two or more metal catalysts, and the catalytic activity is improved by the different reaction mechanisms of the composite catalyst or by increasing the metal active sites on the surface. Perovskite, as a multi-metal oxide, is composed of rare earth metals and transition metals, and has higher thermal stability, chemical stability and structural stability, which is beneficial to reduce the loss of active components and extend the service life. Therefore, perovskite can catalyze gas-phase or solid-phase reactions at high temperatures, and can also catalyze liquid-phase reactions at low temperatures, which makes perovskite widely used in catalysis. However, traditional perovskites have inherent disadvantages such as low specific surface area, low redox potential, easy agglomeration and catalyst deactivation.
[0004] Perovskite can be combined with other materials to prepare perovskite-based composite catalysts, which have synergistic effects between different components. Metal oxides can be used as favorable carriers for the synthesis of perovskite-based composite materials to improve the catalytic degradation efficiency of organic pollutants, but traditional metal oxides have low electrical conductivity, electrochemical activity and catalytic activity.
[0005] Chinese patent CN117623483A discloses the preparation and application of a nickel-doped lanthanum iron perovskite catalyst, which uses photocatalysis combined with H2O2 oxidation technology to achieve the degradation of antibiotic wastewater, and its catalytic efficiency depends on the dual conditions of light and H2O2. Summary of the invention
[0006] The purpose of the present invention is to solve at least one of the above problems and to provide a cobalt sulfide modified iron-based perovskite composite catalyst and a preparation method and application, so as to solve the problems in the prior art that traditional perovskite catalysts have poor degradation effects on antibiotic pollutants and traditional metal oxide carriers have low catalytic activity, thereby achieving the preparation of LaFeO3 perovskite composite catalysts with high specific surface area, multiple active sites and fast reaction rate.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] One of the technical solutions of the present invention is to provide a cobalt sulfide modified iron-based perovskite composite catalyst, wherein the composite catalyst is formed by in-situ growth of CoS2 and CoFe2O4 using LaFeO3 perovskite as a substrate.
[0009] The multi-metal synergistic effect among LaFeO3, CoS2 and CoFe2O4 and the promoting effect of S vacancies on the redox cycle of transition metals Fe and Co can effectively improve the catalytic activity of the catalyst.
[0010] Furthermore, the in-situ growth is achieved by a hydrothermal method.
[0011] The second technical solution of the present invention is to provide a method for preparing the cobalt sulfide modified iron-based perovskite composite catalyst as described above, comprising the following steps:
[0012] S1: Dissolve La salt, Fe salt and organic acid in deionized water, heat and stir until gel-like;
[0013] S2: drying and calcining the gel obtained in step S1 to obtain a LaFeO3 perovskite catalyst;
[0014] S3: dispersing the LaFeO3 perovskite catalyst prepared in step S2 in deionized water, adding Co salt and CH4N2S and stirring to obtain a mixed phase;
[0015] S4: subjecting the mixed phase obtained in step S3 to hydrothermal synthesis, removing the precipitate by centrifugation after the reaction is completed, washing and drying to obtain the cobalt sulfide modified iron-based perovskite composite catalyst.
[0016] Furthermore, the La salt is La(NO3)3·6H2O; the Fe salt is Fe(NO3)2·9H2O; the organic acid is citric acid; and the Co salt is Co(NO3)2·9H2O.
[0017] Furthermore, the molar ratio of the La salt:Fe salt:organic acid is 1:1:(1-2).
[0018] Furthermore, the La salt, Fe salt and organic acid are added to deionized water and ultrasonically treated at room temperature until they are completely dissolved, and the room temperature ultrasonic treatment time is 8 to 12 hours.
[0019] Furthermore, in step S1, the heating is carried out in a water bath, the heating temperature is 80-100° C., and the stirring time is 1-2 h.
[0020] Furthermore, in step S2, the drying temperature is 80-100°C, and the time is 8-18 hours; the calcination temperature is 400-800°C, and the time is 2-6 hours.
[0021] Furthermore, in step S2, the calcination is carried out in a muffle furnace.
[0022] Furthermore, in step S3, the LaFeO3 perovskite catalyst is dispersed in deionized water by ultrasound.
[0023] Furthermore, in step S3, the ratio of the LaFeO3 perovskite mass: Co salt concentration: CH4N2S concentration is 3g: 1 mol / L: (0.5-2) mol / L.
[0024] Furthermore, in step S3, the time of adding Co salt and CH4N2S and stirring is 0.2 to 0.8 h.
[0025] Furthermore, in step S4, the mixed phase is placed in a reaction kettle, and the reaction kettle is placed in an oven to perform a hydrothermal synthesis reaction.
[0026] Furthermore, in step S4, the temperature of the hydrothermal synthesis is 120-200° C., and the hydrothermal time is 6-18 hours.
[0027] Furthermore, in step S4, the separated product is washed with deionized water and ethanol and then placed in a vacuum box to dry.
[0028] The third technical solution of the present invention is to provide an application of the cobalt sulfide modified iron-based perovskite composite catalyst as described above in activating persulfate to degrade antibiotic wastewater.
[0029] Furthermore, the catalytic degradation of antibiotic wastewater is as follows: adding the catalyst of the present invention and persulfate to the wastewater to degrade the wastewater; wherein the amount of the catalyst added is 0.1-0.5 g / L, the concentration of the persulfate is 0.1-0.5 mM, and the pH of the solution is 5-7.
[0030] Furthermore, the persulfate includes any one of peroxymonosulfate (PMS) and peroxydisulfate (PDS).
[0031] Metal sulfides have higher electrical conductivity, electrochemical activity and catalytic activity, making them ideal candidates to replace metal oxides. Transition metal sulfides have superior persulfate activation performance, abundant active sites and high electron mobility. Compared with other transition metal ions, Co 3+ / Co 2+ It has a higher standard reduction potential, which is more conducive to the activation reaction of persulfate. In the field of photocatalysis and supercapacitors, cobalt sulfide has been shown to have higher electron mobility than cobalt-based oxides, accelerating the activation of Co 2+ The electron transition between cobalt sulfide and perovskite can enhance its activation efficiency. Therefore, combining cobalt sulfide with perovskite materials is expected to improve the overall catalytic activity of perovskite.
[0032] This patent invents a cobalt sulfide-modified iron-based perovskite composite catalyst, which increases the specific surface area and redox potential of perovskite, solves the problem of easy agglomeration and easy deactivation, improves the shortcomings of traditional perovskite, and grows CoS2 and CoFe2O4 in situ on it by hydrothermal method to improve the activation effect of persulfate, which is suitable for the treatment of various polluted water bodies. Cobalt sulfide-modified perovskite is only activated by persulfate and does not rely on light, so the reaction conditions are more flexible; and compared with nickel materials, cobalt sulfide usually has higher catalytic activity, especially in redox reactions, it shows strong electron transfer ability.
[0033] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0034] Compared with the prior art, the present invention has the following advantages:
[0035] 1. The present invention simultaneously grows CoS2 and CoFe2O4 on the surface of LaFeO3 through in-situ synthesis technology. The ternary composite material formed by LaFeO3, CoS2 and CoFe2O4 shows a higher reaction rate than a single system, has a higher specific surface area, exposes more active sites, effectively improves the electron transfer rate, and significantly promotes the generation of ROS. The degradation rate of metronidazole reaches up to 96.6% within 20 minutes.
[0036] 2. Iron-based materials are environmentally friendly, low in toxicity and cost-effective, and the variable valence state of iron in perovskite is of great significance in the formation of oxygen defects.
[0037] 3. As a metal sulfide, cobalt sulfide has a high reduction potential, which shows an excellent activation effect on persulfate. The presence of sulfur can not only mediate the redox cycle of transition metals, but also form sulfur vacancies, which significantly accelerates the adsorption and decomposition of PMS, thereby promoting the catalytic degradation of pollutants.
[0038] 4. The present invention prepares the cobalt sulfide modified LaFeO3 composite catalyst by a hydrothermal synthesis method, and the preparation method is simple, efficient and easy to implement. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a flow chart for the preparation of cobalt sulfide modified LaFeO3 composite catalyst.
[0040] Figure 2 SEM images of the LaFeO3 catalyst (A) of Comparative Example 1 and the cobalt sulfide-modified LaFeO3 composite catalyst (B) of Example 3.
[0041] Figure 3 The XRD spectra of the LaFeO3 catalyst of Comparative Example 1 and the cobalt sulfide modified LaFeO3 composite catalyst of Example 3 are shown.
[0042] Figure 4 The kinetic diagram of the degradation of metronidazole by activating PMS using the LaFeO3 catalyst of Comparative Example 1 and the cobalt sulfide modified LaFeO3 composite catalyst of Example 3. DETAILED DESCRIPTION
[0043] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0044] Unless otherwise specified, the experimental reagents and raw materials used in the present invention are commercially available.
[0045] The experimental methods without specific conditions in the following implementations are all selected according to conventional methods and conditions, or according to the product instructions. Unless otherwise specified, the experimental instruments used in the present invention are all conventional experimental instruments in the laboratory.
[0046] A method for preparing a novel cobalt sulfide modified iron-based perovskite composite material, such as Figure 1 As shown, the following steps are included:
[0047] S1: La(NO3)3·6H2O, Fe(NO3)2·9H2O and citric acid were placed in deionized water and sonicated at room temperature until completely dissolved;
[0048] S2: stirring the solution obtained in step S1 in a constant temperature water bath until it reaches a gel state;
[0049] S3: drying the gel obtained in step S2;
[0050] S4: calcining the gel material obtained in step S3 in a muffle furnace to obtain a LaFeO3 perovskite catalyst;
[0051] S5: placing the LaFeO3 prepared in step S4 in deionized water and ultrasonicating the material to fully disperse it;
[0052] S6: placing Co(NO3)2·9H2O and CH4N2S in the mixed solution prepared in step S5 and stirring;
[0053] S7: placing the solution prepared in step S6 into a reaction kettle, and placing the reaction kettle into an oven for hydroheating;
[0054] S8: After the reaction of step S6 is completed, the precipitate is separated by centrifuge, washed with deionized water and ethanol, and the separated product is dried in a vacuum oven to obtain a composite catalyst. Figure 2-4 The present invention is described in detail with reference to the accompanying drawings and embodiments.
[0055] Example 1
[0056] This embodiment provides a cobalt sulfide modified iron-based perovskite composite catalyst and a preparation method thereof:
[0057] S1: 1 mol / L La(NO3)3·6H2O, 1 mol / L Fe(NO3)2·9H2O and 2 mol / L citric acid were placed in 10 mL of deionized water at room temperature and ultrasonicated for 0.5 h at room temperature until completely dissolved;
[0058] S2: Stir the solution obtained in step S1 in a constant temperature water bath at 80° C. for 2 h until it reaches a gel state;
[0059] S3: drying the gel obtained in step S2 at 100° C. for 8 h;
[0060] S4: calcining the gel material obtained in step S3 in a muffle furnace at 500° C. for 3 h to obtain a LaFeO3 perovskite catalyst;
[0061] S5: Weigh 0.3 g of the LaFeO3 perovskite catalyst prepared in step S4 and place it in 50 mL of deionized water and perform ultrasonic treatment for 0.5 h to fully disperse the material;
[0062] S6: Weigh 0.1 mol / L Co(NO3)2·9H2O and 0.05 mol / L CH4N2S into the mixed solution prepared in step S5 and stir for 0.5 h;
[0063] S7: placing the solution prepared in step S6 into a 100 mL reactor, and placing the reactor into an oven for hydrothermal treatment at 180° C. for 8 h;
[0064] S8: After the reaction in step S6 is completed, the precipitate is separated by a centrifuge, washed three times with deionized water and ethanol, and the separated product is dried in a vacuum oven at 60° C. for 24 hours to obtain a composite catalyst.
[0065] Add 50mL of metronidazole solution and 1mM PMS to a conical flask and adjust the pH of the system to 3. Add 0.3g / L of the composite catalyst, mix well and place in a constant temperature shaking shaker (180r / min). Collect 1mL of sample solution at a fixed time point, add 1mL of ethanol to quench the active substance, and 3mL of deionized water for dilution. After filtering through a 0.45μm polyethersulfone filter membrane, use a UV-visible spectrophotometer to measure the absorbance of the solution at a characteristic wavelength of 319nm. The calculation process of the degradation rate is shown in formula (1):
[0066]
[0067] Wherein, C0 (mg / L) is the concentration of the substrate solution before the reaction;
[0068] C t (mg / L) is the concentration of the substrate solution after reaction t min.
[0069] Example 2
[0070] This embodiment provides a cobalt sulfide modified iron-based perovskite composite catalyst and a preparation method thereof:
[0071] S1: 1 mol / L La(NO3)3·6H2O, 1 mol / L Fe(NO3)2·9H2O and 2 mol / L citric acid were placed in 10 mL of deionized water at room temperature and ultrasonicated for 0.5 h at room temperature until completely dissolved;
[0072] S2: Stir the solution obtained in step S1 in a constant temperature water bath at 80° C. for 2 h until it reaches a gel state;
[0073] S3: drying the gel obtained in step S2 at 80°C for 12h;
[0074] S4: calcining the gel material obtained in step S3 in a muffle furnace at 500° C. for 2 h to obtain a LaFeO3 perovskite catalyst;
[0075] S5: Weigh 0.3 g of the LaFeO3 perovskite catalyst prepared in step S4 and place it in 50 mL of deionized water and perform ultrasonic treatment for 0.5 h to fully disperse the material;
[0076] S6: Weigh 0.1 mol / L Co(NO3)2·9H2O and 0.1 mol / L CH4N2S into the mixed solution prepared in step S5 and stir for 0.5 h;
[0077] S7: placing the solution prepared in step S6 into a 100 mL reactor, and placing the reactor into an oven for hydrothermal treatment at 180° C. for 12 h;
[0078] S8: After the reaction in step S6 is completed, the precipitate is separated by a centrifuge, washed three times with deionized water and ethanol, and the separated product is dried in a vacuum oven at 60° C. for 24 hours to obtain a composite catalyst.
[0079] Add 50 mL of metronidazole solution and 1 mM PMS to a conical flask and adjust the pH of the system to 5. Add 0.3 g / L of the composite catalyst, mix well and place in a constant temperature shaking shaker (180 r / min). Collect 1 mL of sample solution at a fixed time point, add 1 mL of ethanol to quench the active substance, and 3 mL of deionized water for dilution. After filtering through a 0.45 μm polyethersulfone filter membrane, use a UV-visible spectrophotometer to measure the absorbance of the solution at a characteristic wavelength of 319 nm. The calculation process of the degradation rate is shown in formula (1):
[0080]
[0081] Wherein, C0 (mg / L) is the concentration of the substrate solution before the reaction;
[0082] C t (mg / L) is the concentration of the substrate solution after reaction t min.
[0083] Example 3
[0084] This embodiment provides a cobalt sulfide modified iron-based perovskite composite catalyst and a preparation method thereof:
[0085] S1: 1 mol / L La(NO3)3·6H2O, 1 mol / L Fe(NO3)2·9H2O and 2 mol / L citric acid were placed in 10 mL of deionized water at room temperature and ultrasonicated for 0.5 h at room temperature until completely dissolved;
[0086] S2: Stir the solution obtained in step S1 in a constant temperature water bath at 80° C. for 2 h until it reaches a gel state;
[0087] S3: drying the gel obtained in step S2 at 100° C. for 12 h;
[0088] S4: calcining the gel material obtained in step S3 in a muffle furnace at 500° C. for 3 h to obtain a LaFeO3 perovskite catalyst;
[0089] S5: Weigh 0.3 g of the LaFeO3 perovskite catalyst prepared in step S4 and place it in 50 mL of deionized water and perform ultrasonic treatment for 0.5 h to fully disperse the material;
[0090] S6: Weigh 0.1 mol / L Co(NO3)2·9H2O and 0.1 mol / L CH4N2S into the mixed solution prepared in step S5 and stir for 0.5 h;
[0091] S7: placing the solution prepared in step S6 into a 100 mL reactor, and placing the reactor into an oven for hydrothermal treatment at 180° C. for 12 h;
[0092] S8: After the reaction in step S6 is completed, the precipitate is separated by a centrifuge, washed three times with deionized water and ethanol, and the separated product is dried in a vacuum oven at 60° C. for 24 hours to obtain a composite catalyst.
[0093] Add 50mL of metronidazole solution and 1mM PMS to a conical flask and adjust the pH of the system to 7. Add 0.3g / L of the composite catalyst, mix well and place in a constant temperature shaking shaker (180r / min). Collect 1mL of sample solution at a fixed time point, add 1mL of ethanol to quench the active substance, and 3mL of deionized water for dilution. After filtering through a 0.45μm polyethersulfone filter membrane, use a UV-visible spectrophotometer to measure the absorbance of the solution at a characteristic wavelength of 319nm. The calculation process of the degradation rate is shown in formula (1):
[0094]
[0095] Wherein, C0 (mg / L) is the concentration of the substrate solution before the reaction;
[0096] C t (mg / L) is the concentration of the substrate solution after reaction t min.
[0097] Example 4
[0098] This embodiment provides a cobalt sulfide modified iron-based perovskite composite catalyst and a preparation method thereof:
[0099] S1: 1 mol / L La(NO3)3·6H2O, 1 mol / L Fe(NO3)2·9H2O and 2 mol / L citric acid were placed in 10 mL of deionized water at room temperature and ultrasonicated for 0.5 h at room temperature until completely dissolved;
[0100] S2: Stir the solution obtained in step S1 in a constant temperature water bath at 80° C. for 2 h until it reaches a gel state;
[0101] S3: drying the gel obtained in step S2 at 100° C. for 18 h;
[0102] S4: calcining the gel material obtained in step S3 in a muffle furnace at 500° C. for 6 h to obtain a LaFeO3 perovskite catalyst;
[0103] S5: Weigh 0.3 g of the LaFeO3 perovskite catalyst prepared in step S4 and place it in 50 mL of deionized water and perform ultrasonic treatment for 0.5 h to fully disperse the material;
[0104] S6: Weigh 0.1 mol / L Co(NO3)2·9H2O and 0.2 mol / L CH4N2S into the mixed solution prepared in step S5 and stir for 0.5 h;
[0105] S7: placing the solution prepared in step S6 into a 100 mL reactor, and placing the reactor into an oven for hydrothermal treatment at 120° C. for 12 h;
[0106] S8: After the reaction in step S6 is completed, the precipitate is separated by a centrifuge, washed three times with deionized water and ethanol, and the separated product is dried in a vacuum oven at 60° C. for 24 hours to obtain a composite catalyst.
[0107] Add 50mL of metronidazole solution and 0.5mM PMS to a conical flask and adjust the pH of the system to 7. Add 0.1g / L of the composite catalyst, mix well and place in a constant temperature shaking shaker (180r / min). Collect 1mL of the sample solution at a fixed time point, add 1mL of ethanol to quench the active substance, and 3mL of deionized water for dilution. After filtering through a 0.45μm polyethersulfone filter membrane, use a UV-visible spectrophotometer to measure the absorbance of the solution at a characteristic wavelength of 319nm. The calculation process of the degradation rate is shown in formula (1):
[0108]
[0109] Wherein, C0 (mg / L) is the concentration of the substrate solution before the reaction;
[0110] C t (mg / L) is the concentration of the substrate solution after reaction t min.
[0111] Example 5
[0112] This embodiment provides a cobalt sulfide modified iron-based perovskite composite catalyst and a preparation method thereof:
[0113] S1: 1 mol / L La(NO3)3·6H2O, 1 mol / L Fe(NO3)2·9H2O and 2 mol / L citric acid were placed in 10 mL of deionized water at room temperature and ultrasonicated for 0.5 h at room temperature until completely dissolved;
[0114] S2: Stir the solution obtained in step S1 in a constant temperature water bath at 80° C. for 2 h until it reaches a gel state;
[0115] S3: drying the gel obtained in step S2 at 100° C. for 12 h;
[0116] S4: calcining the gel material obtained in step S3 in a muffle furnace at 400° C. for 3 h to obtain a LaFeO3 perovskite catalyst;
[0117] S5: Weigh 0.3 g of the LaFeO3 perovskite catalyst prepared in step S4 and place it in 50 mL of deionized water and perform ultrasonic treatment for 0.5 h to fully disperse the material;
[0118] S6: Weigh 0.1 mol / L Co(NO3)2·9H2O and 0.1 mol / L CH4N2S into the mixed solution prepared in step S5 and stir for 0.5 h;
[0119] S7: placing the solution prepared in step S6 into a 100 mL reactor, and placing the reactor into an oven for hydrothermal treatment at 180° C. for 6 h;
[0120] S8: After the reaction in step S6 is completed, the precipitate is separated by a centrifuge, washed three times with deionized water and ethanol, and the separated product is dried in a vacuum oven at 60° C. for 24 hours to obtain a composite catalyst.
[0121] Add 50mL of metronidazole solution and 0.1mM PMS to a conical flask and adjust the pH of the system to 7. Add 0.3g / L of the composite catalyst, mix well and place in a constant temperature shaking shaker (180r / min). Collect 1mL of the sample solution at a fixed time point, add 1mL of ethanol to quench the active substance, and 3mL of deionized water for dilution. After filtering through a 0.45μm polyethersulfone filter membrane, use a UV-visible spectrophotometer to measure the absorbance of the solution at a characteristic wavelength of 319nm. The calculation process of the degradation rate is shown in formula (1):
[0122]
[0123] Wherein, C0 (mg / L) is the concentration of the substrate solution before the reaction;
[0124] C t (mg / L) is the concentration of the substrate solution after reaction t min.
[0125] Example 6
[0126] This embodiment provides a cobalt sulfide modified iron-based perovskite composite catalyst and a preparation method thereof:
[0127] S1: 1 mol / L La(NO3)3·6H2O, 1 mol / L Fe(NO3)2·9H2O and 2 mol / L citric acid were placed in 10 mL of deionized water at room temperature and ultrasonicated for 0.5 h at room temperature until completely dissolved;
[0128] S2: Stir the solution obtained in step S1 in a constant temperature water bath at 80° C. for 2 h until it reaches a gel state;
[0129] S3: drying the gel obtained in step S2 at 100° C. for 12 h;
[0130] S4: calcining the gel material obtained in step S3 in a muffle furnace at 800° C. for 3 h to obtain a LaFeO3 perovskite catalyst;
[0131] S5: Weigh 0.3 g of the LaFeO3 perovskite catalyst prepared in step S4 and place it in 50 mL of deionized water and perform ultrasonic treatment for 0.5 h to fully disperse the material;
[0132] S6: Weigh 0.1 mol / L Co(NO3)2·9H2O and 0.1 mol / L CH4N2S into the mixed solution prepared in step S5 and stir for 0.5 h;
[0133] S7: placing the solution prepared in step S6 into a 100 mL reactor, and placing the reactor into an oven for hydrothermal treatment at 200° C. for 12 h;
[0134] S8: After the reaction in step S6 is completed, the precipitate is separated by a centrifuge, washed three times with deionized water and ethanol, and the separated product is dried in a vacuum oven at 60° C. for 24 hours to obtain a composite catalyst.
[0135] Add 50 mL of metronidazole solution and 1 mM PMS to a conical flask and adjust the pH of the system to 7. Add 0.5 g / L of the composite catalyst, mix well and place in a constant temperature shaking shaker for shaking (180 r / min). Collect 1 mL of the sample solution at a fixed time point, add 1 mL of ethanol to quench the active substance, and 3 mL of deionized water for dilution. After filtering through a 0.45 μm polyethersulfone filter membrane, use a UV-visible spectrophotometer to measure the absorbance of the solution at a characteristic wavelength of 319 nm. The calculation process of the degradation rate is shown in formula (1):
[0136]
[0137] Wherein, C0 (mg / L) is the concentration of the substrate solution before the reaction;
[0138] C t (mg / L) is the concentration of the substrate solution after reaction t min.
[0139] Comparative Example 1
[0140] This comparative example provides an unmodified iron-based perovskite catalyst and a preparation method thereof:
[0141] S1: 1 mol / L La(NO3)3·6H2O, 1 mol / L Fe(NO3)2·9H2O and 2 mol / L citric acid were placed in 10 mL of deionized water at room temperature and ultrasonicated for 0.5 h at room temperature until completely dissolved;
[0142] S2: Stir the solution obtained in step S1 in a constant temperature water bath at 80° C. for 2 h until it reaches a gel state;
[0143] S3: drying the gel obtained in step S2 at 100° C. for 12 h;
[0144] S4: calcining the gel material obtained in step S3 in a muffle furnace at 500° C. for 3 h to obtain a LaFeO 3 perovskite catalyst.
[0145] Add 50mL of metronidazole solution and 1mM PMS to a conical flask and adjust the pH of the system to 7. Add 0.3g / L of the composite catalyst, mix well and place in a constant temperature shaking shaker (180r / min). Collect 1mL of sample solution at a fixed time point, add 1mL of ethanol to quench the active substance, and 3mL of deionized water for dilution. After filtering through a 0.45μm polyethersulfone filter membrane, use a UV-visible spectrophotometer to measure the absorbance of the solution at a characteristic wavelength of 319nm. The calculation process of the degradation rate is shown in formula (1):
[0146]
[0147] Wherein, C0 (mg / L) is the concentration of the substrate solution before the reaction;
[0148] C t (mg / L) is the concentration of the substrate solution after reaction t min.
[0149] Comparative Example 2
[0150] This comparative example provides a cobalt sulfide modified iron-based perovskite composite material and a preparation method thereof. The difference from the embodiment is that PMS is not added during the catalyst performance determination, so that the cobalt sulfide modified iron-based perovskite composite catalyst only has an adsorption effect on metronidazole and does not have a catalytic degradation effect:
[0151] S1: 1 mol / L La(NO3)3·6H2O, 1 mol / L Fe(NO3)2·9H2O and 2 mol / L citric acid were placed in 10 mL of deionized water at room temperature and ultrasonicated for 0.5 h at room temperature until completely dissolved;
[0152] S2: Stir the solution obtained in step S1 in a constant temperature water bath at 80° C. for 2 h until it reaches a gel state;
[0153] S3: drying the gel obtained in step S2 at 100° C. for 12 h;
[0154] S4: calcining the gel material obtained in step S3 in a muffle furnace at 500° C. for 3 h to obtain a LaFeO3 perovskite catalyst;
[0155] S5: Weigh 0.3 g of the LaFeO3 perovskite catalyst prepared in step S4 and place it in 50 mL of deionized water and perform ultrasonic treatment for 0.5 h to fully disperse the material;
[0156] S6: Weigh 0.1 mol / L Co(NO3)2·9H2O and 0.1 mol / L CH4N2S into the mixed solution prepared in step S5 and stir for 0.5 h;
[0157] S7: placing the solution prepared in step S6 into a 100 mL reactor, and placing the reactor into an oven for hydrothermal treatment at 180° C. for 12 h;
[0158] S8: After the reaction in step S6 is completed, the precipitate is separated by a centrifuge, washed three times with deionized water and ethanol, and the separated product is dried in a vacuum oven at 60° C. for 24 hours to obtain a composite catalyst.
[0159] Add 50 mL of metronidazole solution to a conical flask and adjust the pH of the system to 7. Add 0.3 g / L of the composite catalyst, mix well and place in a constant temperature shaking shaker (180 r / min). Collect 1 mL of sample solution at a fixed time point, add 1 mL of ethanol to quench the active substance, and 3 mL of deionized water for dilution. After filtering through a 0.45 μm polyethersulfone filter membrane, use a UV-visible spectrophotometer to measure the absorbance of the solution at a characteristic wavelength of 319 nm. The calculation process of the degradation rate is shown in formula (1):
[0160]
[0161] Wherein, C0 (mg / L) is the concentration of the substrate solution before the reaction;
[0162] C t (mg / L) is the concentration of the substrate solution after reaction t min.
[0163] The preparation parameters of Examples 1-6 and Comparative Examples 1-2 are shown in Table 1:
[0164] Table 1 Preparation process parameters of Examples 1-6 and Comparative Examples 1-2
[0165]
[0166] Figure 2 SEM images of the LaFeO3 catalyst (A) of Comparative Example 1 and the cobalt sulfide-modified LaFeO3 composite catalyst (B) of Example 3. Figure 2 It can be clearly seen that the LaFeO3 catalyst of Comparative Example 1 has formed a state of agglomeration and accumulation, and has a large number of irregular pores on the surface. However, the surface macropores of the cobalt sulfide modified LaFeO3 composite catalyst of Example 3 have basically disappeared, and the surface is evenly covered with a large number of CoFe2O4 and CoS2 particles, and has good dispersibility, which is conducive to increasing the specific surface area of the material, exposing more active sites, and improving the catalytic activity of the material.
[0167] Figure 3 The XRD spectra of the LaFeO3 catalyst of Comparative Example 1 and the cobalt sulfide modified LaFeO3 composite catalyst of Example 3 show that the characteristic peaks of LaFeO3 can be observed in both catalysts. Compared with the LaFeO3 catalyst of Comparative Example 1, the intensity of the characteristic peaks of perovskite in the cobalt sulfide modified LaFeO3 composite catalyst of Example 3 is significantly weakened, which is because the Fe ions in LaFeO3 are leached out and combined with Co and S to form CoS2 and CoFe2O4, respectively, and cover the surface of LaFeO3.
[0168] The cobalt sulfide modified LaFeO3 catalyst prepared in Example 1-6 and the catalyst prepared in Comparative Example 1-2 were used to perform degradation experiments on wastewater containing metronidazole. The specific experimental parameters and degradation rates are shown in Table 2:
[0169] Table 2 Degradation parameters of Examples 1-6 and Comparative Examples 1-2 and catalytic degradation efficiency of metronidazole
[0170]
[0171] As shown in Examples 1-6 of Table 2, the degradation rate of metronidazole in the cobalt sulfide modified LaFeO3 activated PMS catalyst system reached 96.6% within 20 min under the conditions of reaction temperature of 25°C, PMS concentration of 1 mM, catalyst dosage of 0.3 g / L, initial solution pH of 7, and initial metronidazole concentration of 20 mg / L.
[0172] (Example 3). As can be seen from Comparative Example 1, compared with pure perovskite, the catalytic performance of cobalt sulfide modified perovskite is significantly improved. Under the same degradation conditions, the degradation rate of metronidazole by cobalt sulfide modified perovskite (96.6%) is better than that of pure perovskite (66.7%). As can be seen from Comparative Example 2, when PMS is not added, cobalt sulfide modified perovskite has only a slight adsorption performance (18.7%) for metronidazole, so the activation effect of the catalyst on PMS is very significant.
[0173] like Figure 4 As shown, Figure 4 The effect of activating PMS to degrade metronidazole by the LaFeO3 catalyst of comparative example 1 and the cobalt sulfide modified LaFeO3 composite catalyst of example 3 is compared. It can be found that after 20 minutes of reaction, the degradation efficiency of metronidazole by the LaFeO3 catalyst of comparative example 1 is only about 64%, while after modification with cobalt sulfide, the degradation efficiency of metronidazole by the cobalt sulfide modified LaFeO3 composite catalyst of example 3 is significantly improved, and the degradation efficiency of metronidazole reaches 96.6% at 15 minutes.
[0174] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A cobalt sulfide modified iron-based perovskite composite catalyst, characterized in that: The composite catalyst is formed by in-situ growth of CoS2 and CoFe2O4 using LaFeO3 perovskite as a substrate.
2. A method for preparing the cobalt sulfide modified iron-based perovskite composite catalyst as claimed in claim 1, characterized in that: The following steps are involved: S1: Dissolve La salt, Fe salt and organic acid in deionized water, heat and stir until gel-like; S2: drying and calcining the gel obtained in step S1 to obtain a LaFeO3 perovskite catalyst; S3: dispersing the LaFeO3 perovskite catalyst prepared in step S2 in deionized water, adding Co salt and CH4N2S and stirring to obtain a mixed phase; S4: subjecting the mixed phase obtained in step S3 to hydrothermal synthesis, and after the reaction is completed, removing the precipitate by centrifugation, washing and drying to obtain the cobalt sulfide modified iron-based perovskite composite catalyst.
3. The method for preparing a cobalt sulfide modified iron-based perovskite composite catalyst according to claim 2, characterized in that: The La salt is La(NO3)3·6H2O; the Fe salt is Fe(NO3)2·9H2O; the organic acid is citric acid; and the Co salt is Co(NO3)2·9H2O.
4. The method for preparing a cobalt sulfide modified iron-based perovskite composite catalyst according to claim 2, characterized in that: In step S1, the molar ratio of La salt:Fe salt:organic acid is 1:1:(1-2).
5. The method for preparing a cobalt sulfide modified iron-based perovskite composite catalyst according to claim 2, characterized in that: In step S1, the heating is carried out in a water bath, the heating temperature is 80-100° C., and the stirring time is 1-2 hours.
6. The method for preparing a cobalt sulfide modified iron-based perovskite composite catalyst according to claim 2, characterized in that: In step S2, the drying temperature is 80-100°C and the time is 8-18 hours; the calcination temperature is 400-800°C and the time is 2-6 hours.
7. The method for preparing a cobalt sulfide modified iron-based perovskite composite catalyst according to claim 2, characterized in that: In step S3, the ratio of the LaFeO3 perovskite mass: Co salt concentration: CH4N2S concentration is 3g: 1 mol / L: (0.5-2) mol / L.
8. The method for preparing a cobalt sulfide modified iron-based perovskite composite catalyst according to claim 2, characterized in that: In step S4, the temperature of the hydrothermal synthesis is 120-200° C., and the hydrothermal time is 6-18 hours.
9. Use of the cobalt sulfide modified iron-based perovskite composite catalyst as claimed in claim 1 in activating persulfate to degrade antibiotic wastewater.
10. The use of a cobalt sulfide modified iron-based perovskite composite catalyst according to claim 9, characterized in that: The catalytic degradation of antibiotic wastewater comprises: adding the catalyst of the present invention and persulfate to the wastewater to degrade the wastewater; wherein the amount of the catalyst added is 0.1-0.5 g / L, the concentration of the persulfate is 0.1-0.5 mM, and the pH of the solution is 5-7.
Citation Information
Patent Citations
Application of nickel-doped lanthanum-iron perovskite in degradation of antibiotics
CN117623483A